Developing a Social Media-Based Communication System Between Rural Healthcare Providers and Expert Medical Personnel in Bokeo Province, Laos PDR - Kapheak , Krissana; Theerawasttanasiri , Nonthaphat; Khumphoo, Potchara; Sriwongphan, Rungrasami; Ritthimon, Wanchalerm; Chayaseng, Chansy; Bounmaseng, Phouangphet; Pangsri, Ninrat; Wungrath, Jukkrit (Journal of Population and Social Studies [JPSS], 2024)
This qualitative study investigates the development of a social media-based communication system designed to enhance interprofessional communication in Maternal and Child Health (MCH) services between rural healthcare providers and expert medical personnel (EMP) in Bokeo Province, Laos. The study addresses the issue of high maternal mortality rates attributed to poor infrastructure and the lack of timely medical interventions. It proposes using WhatsApp, a popular social media platform in Laos, to bridge this communication gap. Employing a participatory action research approach, the study involved 269 healthcare providers and four EMPs in focus group discussions. These discussions were instrumental in identifying unique communication challenges and potential solutions. Thematic analysis of the data revealed significant barriers to seeking expert advice and underscored the potential of digital health solutions like WhatsApp in overcoming these obstacles. To successfully implement such a system, considerations must include privacy, professionalism, consistent internet connectivity, adequate training, and clear usage guidelines. This study informs the development of a context-specific, comprehensive strategy that integrates technological, infrastructural, financial, educational, and cultural elements to enhance MCH outcomes in remote areas of Laos.